Transcending Paradigm: Bridging Spirituality and Modern Science in the Thoughts of Nasr, al-Attas, and al-Faruqi - Zuhri, Mishbah Khoiruddin; Mundhir, Mundhir (Jurnal Theologia, 2023)
The research examines the transcending paradigm as a crucial intellectual approach, with scholars like Seyyed Hossein Nasr, Syed Muhammad Naquib al-Attas, and Ismail Raji al-Faruqi proposing a synthesis of Islamic spiritual principles with modern scientific inquiry. This paradigm aims to bridge the gap between science and spirituality, advocating for a unified model that respects Islamic metaphysical traditions while embracing empirical scientific advancements. Through a systematic comparative and analytical approach, the research thoroughly examines and critiques the philosophical foundations and theoretical frameworks presented by Nasr, al-Attas, and al-Faruqi. This study's synthesis of these scholars' perspectives makes it unique, providing insights into their efforts to move beyond traditional academic paradigms. Their contributions argue for a coherent framework harmonizing divine unity and cosmic understanding. They assert that true knowledge encompasses both the material and the transcendent, offering a holistic and spiritually enriched scientific perspective. This article contributes to enhancing the Islamic intellectual tradition by presenting a model deeply rooted in cultural values and responsive to the complexities of the modern scientific era.